TGF-β enhances alcohol dependent hepatocyte damage via down-regulation of alcohol dehydrogenase I - Ciuclan, Loredana Ioana; Ehnert, Sabrina; Ilkavets, Iryna; Weng, Honglei; Gaitantzi, Haristi; Tsukamoto, Hidekazu; Ueberham, Elke; Meindl-Beinker, Nadja M.; Singer, Manfred V.; Breitkopf-Heinlein, Katja; Dooley, Steven (Journal of hepatology, 2010)
BACKGROUND & AIMS: Adverse alcohol effects in the liver involve oxidative metabolism, fat deposition and release of fibrogenic mediators, including TGF-beta. The work presents an assessment of liver damaging cross-talk between ethanol and TGF-beta in hepatocytes. - METHODS: To investigate TGF-beta effects on hepatocytes, microarray analyses were performed and validated by qRT-PCR, Western blot analysis and immunohistochemistry. The cellular state was determined by assessing lactate dehydrogenase, cellular glutathione, reactive oxygen species, lipid peroxidation and neutral lipid deposition. RNA interference was used for gene silencing in vitro. - RESULTS: TGF-beta is induced in mouse livers after chronic ethanol insult, enhances ethanol induced oxidative stress and toxicity towards cultured hepatocytes plus induces lipid-, oxidative stress metabolism- and fibrogenesis-gene expression signatures. Interestingly, TGF-beta down-regulates alcohol metabolizing enzyme Adh1 mRNA in cultured hepatocytes and liver tissue from TGF-beta transgenic mice via the ALK5/Smad2/3 signalling branch, with Smad7 as a potent negative regulator. ADH1 deficiency is a determining factor for the increased lipid accumulation and Cyp2E1 dependent toxicity in liver cells upon alcohol challenge. Further, ADH1 expression was decreased during liver damage in an intragastric ethanol infusion mouse model. - CONCLUSION: In the presence of ethanol, TGF-beta displays pro-steatotic action in hepatocytes via decreasing ADH1 expression. Low ADH1 levels are correlated with enhanced hepatocyte damage upon chronic alcohol consumption by favoring secondary metabolic pathways.
Gesehen am 23.03.2023